2021
DOI: 10.2147/nss.s295030
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Patients with Borderline Personality Disorder

Abstract: Objective Both sleep disorders and BPD are prevalent in the population, and one is often a comorbidity of the other. This narrative review aims to assess contemporary literature and scientific databases to provide the current state of knowledge about sleep disorders in patients with borderline personality disorder (BPD) and clinical suggestions for managing sleep disorders in BPD patients and future research direction. Methods Articles were acquired via PubMed and Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…One study reported that compared with non-BPD individuals with NSSI, BPD individuals with NSSI are more prone to severe depression and suicidal behavior ( 48 ). Some studies have noted that people with BPD have a higher risk of NSSI than the general population ( 49 , 50 ), and there is an interaction between BPD and NSSI ( 51 ). Our analysis showed that BPD tendencies are significantly positively correlated with NSSI in PTSD students, which further confirms that BPD tendencies can increase the risk of NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that compared with non-BPD individuals with NSSI, BPD individuals with NSSI are more prone to severe depression and suicidal behavior ( 48 ). Some studies have noted that people with BPD have a higher risk of NSSI than the general population ( 49 , 50 ), and there is an interaction between BPD and NSSI ( 51 ). Our analysis showed that BPD tendencies are significantly positively correlated with NSSI in PTSD students, which further confirms that BPD tendencies can increase the risk of NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…People diagnosed with personality disorder (PD) commonly describe poor quality sleep, with evidence pointing to a prevalence of insomnia of around 70% (Selby, 2013; Van Veen et al, 2017; Vanek et al, 2021). Because people with PD (also frequently referred to as complex emotional needs [CEN]) make up 30%–50% of all patients in secondary mental health services, sleep disturbance in PD is a common presentation in the psychiatric clinic (Newton‐Howes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbed sleep is thus a highly important factor in BPD severity and recovery. BPD patients often experience severe sleep disturbances ( DeShong and Tucker, 2019 ; Schredl et al, 2012 ; Vanek et al, 2021 ). A recent meta-analytic review showed both subjective (e.g.…”
Section: Introductionmentioning
confidence: 99%